Sustainable energy opportunities in localised food production and transportation: A case study of bread in the UK - López-Avilés, A; Veldhuis, J; Leach, M; Yang, A (Elsevier, 2019)
Re-distributed manufacturing (RDM) is of high economic and political interest and is associated with rapid technological, environmental, political, regulatory and social changes in the UK. RDM of food raises opportunities and questions around the local nexus of food, energy and water. Considering these together can provide opportunities for rationalising resource utilisation, production, and consumption while contributing to shared prosperity between business, society and natural ecosystems. This paper concentrates on the energy–food aspects of the nexus for RDM by focusing on the case study of bread manufacturing and transportation in the UK. A detailed analysis of the energy requirements and environmental impacts of centralised bread production and transportation compared with localised options for re-distributed bread manufacturing is undertaken. This is achieved by building on existing literature and developing a series of bread-energy system configurations to model energy usage and green-house gas (GHG) emissions at the large (centralised), medium and small scales. Results from the analysis indicate that energy use and emissions can in some instances increase as a result of losing economies of scale through downscaling bread manufacturing. However, the analysis shows that overall energy use and emissions along the bread supply chain are dominated by transportation stages. Thus, RDM opens up new opportunities for reductions in overall energy consumption and emissions, for example by using low carbon vehicles for the transportation of bread and flour at the medium and small scales. Major energy use and emission reductions could also be achieved by reducing car usage if more consumers buy in local bakeries. The configurations also consider energy use for various bread wastage conditions. Assuming that buying more frequently in local bakeries only the bread that is consumed helps avoiding bread wastage, this would lead to reduced bread purchasing and bread manufacturing, which translates to reductions in energy use and emissions in the modelled configurations. Existing data demonstrate that there is a wide diversity across different manufacturing sites in the energy use and associated emissions per loaf of bread produced. The study highlights the opportunities for improvement in the sector if plant move towards the best available manufacturing technologies and practices, and this may be more practical for smaller scale operations. Two hypothetical bread production scenarios show that a greater share of the UK’s bread being produced locally could result in a reduction in overall energy consumption and emissions.